Pengelolaan Lahan Parkir Untuk Peningkatan Pendapatan Asli Daerah - Yohanis Endes Teturan; Hubertus Oja (SOCIETAS, 2023)
Wamanggu Market as it should provide adequate parking, but the fact is that Wamanngu Market has not been able to provide adequate parakir land for vehicles of people visiting the market. The purpose of the research study was to formulate a parking lot management model at the Wamanggu Market to increase local income. The research method uses a qualitative approach. Data collection techniques: observation, interviews, documentation, and FGD, while data analysis uses Data reduction, Data Display, Data verification. The results showed that the parking lot at Wamanggu Market has not been able to accommodate vehicles to park in the parking lot provided so that many people park their vehicles outside the market area, including on the road body around the market area. This has an impact on pad being less than optimal because vehicles that park outside the market area are not subject to payment of parking levies. The volume provided has not been balanced with the number of vehicles that want to park, parking facilities in the form of guard posts, and portals are no longer functioning and do not have parking signs. The density of vehicles using the parking lot makes parking attendants have the ability to arrange vehicles to use the parking lot, of course, it will have an impact on the parking levy. The need for parking space has been converted to a place for selling merchants so that it needs integrated parking management between the needs of parking spaces and the parking facilities provided.v